Código amixer del castellano - Minaya Aguilar, Yeni Yanet (2019)
It addresses from a linguistic point of view the general characteristics of the Spanish amixer code, (or Spanish amixer), which is a graphic code used by teenagers on the Internet, specifically on Facebook, its sources and basic training mechanisms, based on the analysis of a linguistic corpus. A description of the amixer and social media social group is made to extend the approach to this code.